Comprehensive scale model for LMFBR reactor assembly thermal hydraulics. (7th February 2008) - Padmakumar, G.; Prakash, V.; Banerjee, I.; Thirumalai, M.; Babu, C.; Prabhakar, R.; Vaidyanathan, G.
The construction of the 500 MWe Prototype Fast Breeder Reactor (PFBR) is underway at Kalpakkam, India. This liquid sodium-cooled reactor is a pool-type reactor with two secondary loops. Experimental investigations have been carried out to understand the complex flow, temperature patterns and flow-induced vibration characteristics. To enhance the confidence in the design of the components immersed in the pool of the reactor and to reduce the scale effects, a large scale model was constructed. The Scale Model for Reactor Thermal Hydraulics (SAMRAT) is a one-by-four scaled-down model of the reactor assembly of PFBR. This model is a unique one in that it attempts to investigate multiple phenomena using a single model. This paper describes the details of the model – the scaling criteria adopted, the simulation for each study, and the methodology of the study and the salient features of the model – and examines the results.